2011
DOI: 10.1177/0145482x1110500705
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Perceived Social Support with Well-Being in Adults with Visual Impairments

Abstract: The relationship between perceived social support and multiple indicators of well-being in adults with visual impairments was investigated. The results included significant correlation of social support and depressive symptoms, satisfaction with life, as well as with physical, psychological, economic, family, and social well-being. Implications for future research and practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 21 publications
1
42
0
14
Order By: Relevance
“…Adults with VI seemingly display more depressive symptoms and less well-being than individuals without disabilities (Cimarolli, 2006; Guerette & Smedema, 2011). Different theoretical perspectives have dominated depression research, including biological, cognitive, life-stress, interpersonal, and developmental psychopathology perspectives (Hammen, 1992; Rudolph et al, 2000; Spence, Sheffield, & Donovan, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Adults with VI seemingly display more depressive symptoms and less well-being than individuals without disabilities (Cimarolli, 2006; Guerette & Smedema, 2011). Different theoretical perspectives have dominated depression research, including biological, cognitive, life-stress, interpersonal, and developmental psychopathology perspectives (Hammen, 1992; Rudolph et al, 2000; Spence, Sheffield, & Donovan, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, functional limitations and social support are often identified as important factors associated with depressive symptoms among visually impaired older adults (Beekman et al , 1995; Rovner et al , 1996; Lebowitz et al , 1997; Penninx et al , 1998; Hybels et al , 2001; Rovner and Casten, 2002; Guerette and Smedema, 2011; Rees et al , 2013). For example, visually impaired older adults often have serious functional limitations associated with depressive symptoms (Branch et al , 1989; Keller et al , 1999; Brody et al , 2001; Burmedi et al , 2002; West et al , 2002; Jang et al , 2003; Schilling et al , 2011; Hochberg et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all centenarians were rated as having visual difficulties and receiving social support. Social support relates to the SWB of people with visual impairments more strongly than variables measuring visual function (Guerette and Smedema, ; Huurre et al , ; Papadopoulos et al , ; Pinquart and Pfeiffer, ). However, centenarians who had severe and average levels of visual impairment tended to report higher levels of depression than those with better vision even if they had social support.…”
Section: Discussionmentioning
confidence: 99%
“…Extant literature examining social support for adults with visual impairments has shown that social support relates more strongly to SWB in people with visual impairments than other variables measuring visual function (Guerette and Smedema, 2011;Huurre et al, 1999;Papadopoulos, et al, 2014;Pinquart and Pfeiffer, 2013). However, few studies have focused on older adults (e.g., Court et al, 2014;Hong, et al, 2015).…”
mentioning
confidence: 99%